Oblicz wartość liczbową wyrażeń algebraicznych:

a) 2b + a dla a = -1, b = 1
b) x² - 1 dla x = 3
c) (2 + y) × x dla x = 2, y = -4
d) 3a + 4b dla a = 2, b = -½
e) 2a² - b dla a = 1, b = -1
f) ½(a + b) dla a = 4, y = -2
g) 3xy - 2 dla x = 4, y = -½

(proszę o odpowiedzi pisemne)


Odpowiedź :

a) 2*1+(-1)=2-1=1
b) 3²-1=9-1=8
c)(2-4)*2=-2*2=-4
d)3*2+4*(-1/2)=6-2=4
e)2*1²+1=2+1=3
f)½(4-2)=½*2=1
g)3*4*(-½)=-6
a)1
b)8
c)-4(nie wiem dokładnie)
d)8
f)1
g)4
a)2b + a dla a=-1, b=1
2*1 -1 = 1

b)3² -1 = 8

c)-2*2=-4

d)6-2 = 4

e)2-1 = 1

f)1/2 * 6 = 3

g)3*4*-½ -2 = 12*-½-2 = -6-2 = -8